Pertanggungjawaban Hukum Nahkoda yang Berlayar tanpa Izin dan Mengakibatkan Kerusakan Jembatan (Studi Putusan Nomor 5319 K/Pid.Sus/2025) - Rode Parohon Santoso Hutabarat; Suriyanto Suriyanto (FOCUS, 2026)
In the maritime sector, the Sailing Approval Letter (Surat Persetujuan Berlayar / SPB) serves as a fundamental legal instrument to ensure vessel seaworthiness, safety, and orderly shipping activities. The SPB is not merely an administrative requirement but a mandatory prerequisite before a vessel may commence a voyage. This study analyzes the legal liability of a ship captain who sailed without an SPB and caused damage to a bridge, as examined in Supreme Court Decision Number 5319 K/Pid.Sus/2025, and evaluates whether the judges’ legal considerations align with principles of justice and applicable legal norms. The findings indicate that sailing without an SPB may result in administrative, criminal, and civil liability, particularly when the act causes damage to public infrastructure. The Supreme Court held that sailing without an SPB constitutes a serious criminal offense due to the substantial risks posed to maritime safety and public facilities. The decision affirms the principle of individual criminal responsibility of the ship captain and reinforces the supervisory authority of the harbormaster. Moreover, it provides a deterrent effect and underscores the importance of strict compliance with maritime regulations to ensure safety, legal certainty, and the protection of public interests in national shipping.